2016
DOI: 10.1021/acsami.6b05354
|View full text |Cite
|
Sign up to set email alerts
|

Cu0.89Zn0.11O, A New Peroxidase-Mimicking Nanozyme with High Sensitivity for Glucose and Antioxidant Detection

Abstract: Nanomaterial-based enzyme mimetics (nanozymes) is an emerging field of research that promises to produce alternatives to natural enzymes for a variety of applications. The search for the most cost-effective and efficient inorganic nanomaterials, such as metal oxides, cannot be won by pristine CuO. However, unlike CuO, the Zn-doped CuO (Zn-CuO) nanoparticles reported in this paper reveal superior peroxidase-like enzyme activity. This places Zn-CuO in a good position to participate in a range of activities aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(117 citation statements)
references
References 46 publications
3
113
0
1
Order By: Relevance
“…Metal doping for enhanced peroxidase‐like activity of CuO NPs was also studied by researcher. In Gedanken's works, they reported the Zn‐doped CuO NPs (Zn‐CuO NPs) with enhanced peroxidase‐like activity and applied to colorimetric glucose biosensor. Results showed that the Zn‐CuO NPs had higher affinity for H 2 O 2 and TMB than CuO and HPR.…”
Section: Glucose Biosensormentioning
confidence: 81%
See 1 more Smart Citation
“…Metal doping for enhanced peroxidase‐like activity of CuO NPs was also studied by researcher. In Gedanken's works, they reported the Zn‐doped CuO NPs (Zn‐CuO NPs) with enhanced peroxidase‐like activity and applied to colorimetric glucose biosensor. Results showed that the Zn‐CuO NPs had higher affinity for H 2 O 2 and TMB than CuO and HPR.…”
Section: Glucose Biosensormentioning
confidence: 81%
“…The doped Mo not only causes more oxygen vacancies but also induce a smaller size and a bigger pore radius of Mo‐doped CeO 2 NPs. The use of metal doping method to tune the nanomaterial's activity was also demonstrated in many other researches …”
Section: Tunable Peroxidase‐like Activity Of Nanomaterialsmentioning
confidence: 93%
“…A recent study, performed by Gao et al, found that the Fe 3 O 4 magnetic nanoparticles (MNPs) were intrinsically active catalyst for some oxidation reactions, being similar to natural horseradish peroxidase (HRP) [57]. The peroxidase-like nature of Fe 3 O 4 MNPs was employed to replace the enzyme HRP used in H 2 O 2 detection and immune-absorbent assay and was also explored for the applications in the degradation of phenolic and aniline compounds [58]. Another application of Iron oxide as peroxidase including diagnostic kit for hydrogen peroxide (H 2 O 2 ) and glucose detection [59].…”
Section: Iron Oxide-based Nanomaterialsmentioning
confidence: 99%
“…Also, another study shows cupric oxide nanoparticle can be used as chemiluminescence cholesterol sensor for detection via peroxidase mimicking [81,85]. Zn-Cuo material is used as a peroxidase to detect three antioxidants tannic acid, tartaric acid and ascorbic acid in addition to glucose detection [58,86], as well as Zn-Cu NPs, when compared to the mentioned antibodies have some potential to act like these antibodies [58]. However, Yan Xo et al showed Cu 2þ as an oxidase mimic is more efficient than Cu/Cuo nanoparticles for histidine detection even in serum or urea detention in presence of O-phenylenediamine (OPD) [59].…”
Section: Cobalt Oxide As Catalase and Peroxidasementioning
confidence: 99%
“…It has been well documented by Nagvenkar et al[47] that the intrinsic peroxidase activity of Cu 0.89 Zn 0.11 O is superior over CuO against typical substrates like TMB, OPD, and ABTS, in presence of H 2 O 2 . Fluorescence and ESR techniques were used to demonstrate the mechanism of action of Zn-CuO.…”
mentioning
confidence: 95%